2012
DOI: 10.1016/j.enpol.2012.02.066
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into recent proposals for a revised definition of zero carbon homes in the UK

Abstract: A rapid transition to 'zero carbon' building was announced by the UK Government in December 2006 as a key step forward in reducing the Green House Gas (GHG) emissions from the domestic and non-domestic sectors. This paper elaborates on whether the revised definition of 'zero carbon' dwellings in the UK (2009) and the approach to implementing this policy, advocated by the Zero Carbon Hub (ZCH) , is coherent with overarching climate change and energy policies. Further, the paper examines the barriers to adopting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 9 publications
0
27
0
1
Order By: Relevance
“…Over the period when changes to definitions of zero carbon homes were proposed in the UK (2010-2015), research supported the view that in order to obtain clear and consistent reductions in long-term energy demand, that the most viable option would be to rely on Passive House or an equivalent standard [33]. This has also been confirmed by other studies which indicated that the development of techniques using such standards could effectively help deliver energy saving and also satisfy client requirements [34].…”
Section: Review Of Previous Researchmentioning
confidence: 81%
“…Over the period when changes to definitions of zero carbon homes were proposed in the UK (2010-2015), research supported the view that in order to obtain clear and consistent reductions in long-term energy demand, that the most viable option would be to rely on Passive House or an equivalent standard [33]. This has also been confirmed by other studies which indicated that the development of techniques using such standards could effectively help deliver energy saving and also satisfy client requirements [34].…”
Section: Review Of Previous Researchmentioning
confidence: 81%
“…The standard requires adherence to specific criteria; most notably annual maximum space heating requirements of 15 kWh/m 2 , maximum annual primary energy of 120 kWh/m 2 , utilisation of Mechanical Ventilation with Heat Recovery (MVHR) and an air tightness (n50) of less than 0.6 h −1 [9]. Proposals have been made for the Passivhaus standard or similar stringent nonresidential standard to be utilised as mandatory requirements for all new buildings by the European Commission [10,11]. However, questions remain concerning the applicability of the Passivhaus standard in the UK in which there are key differences, for example, climate, space standards and procurement.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these challenges are linked to concerns over certainty, institutional capacity and market responsiveness. Whilst on the one hand there are real concerns over the mainstream implementation, regulatory compliance and long term performance and maintenance of these largely untested technologies in new buildings (DCLG, 2006a; Power, 2008;Greenwood, 2010;McLeod et al, 2012) on the other, there is unease over the time it might take for changing consumer preferences to be reflected in price signals (Parag and Darby, 2009) and whether lenders and valuers will incorporate environmental premiums in property valuation techniques (Lorenz and Lutzkendorf, 2008;Meins et al, 2010;NHBC Foundation, 2012). Whilst there is no clear position in the literature on real consumer demand for zero carbon homes, industry thinking tends to argue for a more consumer-centric policy framework for encouraging consumers to value and pursue energy efficient homes.…”
Section: ! a Contested Transition?mentioning
confidence: 99%
“…The ability of speculative housebuilders to respond to this challenge remains untested and is the subject of the empirical interrogation that follows. (DCLG, 2007;McLeod et al, 2012). ¥!…”
mentioning
confidence: 99%